Secondary Vesical Calculus Resulting from Migration of an Intrauterine Contraceptive Device - Suvarna Vagholkar; Ketan Vagholkar (Case Reports in Obstetrics and Gynecology)
Intrauterine contraceptive device (IUCD) is the commonest form of contraception used in view of less systemic side effects. However, there are a multitude of local complications caused by it. Of all the local complications described, migration of the device into adjacent organs is the most morbid of all complications. A patient presenting with history of loss or disappearance of the intrauterine contraceptive device accompanied by urinary symptoms should raise the doubt of a migrated device with the formation of a secondary calculus. This prompts further radiological investigations and merits surgical intervention either endourologically or by open surgery depending upon the merits of the case. A case report elucidating this fact is presented.